EFL STUDENTS’ PERCEPTIONS OF ANONYMOUS PARTICIPATION TOOLS IN REDUCING ANXIETY - Rumaisha Aziza Yasmin; Putu Dian Danayanti Degeng (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Digital interactive platforms with various interactive features are now gaining attention as a way to support student engagement in EFL classes. However, studies specifically exploring their anonymous participation features are still limited, especially in Indonesian higher education. This study examines EFL students' perceptions of anonymous participation features in reducing anxiety and improving classroom interaction. Using a quantitative descriptive approach, the study involved 94 English Language Education students at a university in Malang. Data were collected through an 11-item Likert-scale questionnaire distributed via Google Forms, which was then analyzed using IBM SPSS Statistics 32. The results showed positive responses across all indicators, with average scores ranging from 4.01 to 4.41. Participating anonymously has been shown to provide a sense of security from the anxiety of negative evaluation. Anonymity has also been shown to be effective in increasing engagement and the quality of classroom interactions, making it a viable learning strategy for EFL lecturers at Indonesian universities to create more comfortable and inclusive classrooms. ABSTRAK Platform interaktif digital dengan berbagai fitur interaktif kini banyak menarik perhatian sebagai cara untuk mendukung keterlibatan siswa di kelas EFL. Namun, studi yang meneliti secara khusus fitur partisipasi anonimnya masih terbatas, terutama di pendidikan tinggi Indonesia. Studi ini meneliti persepsi mahasiswa EFL tentang fitur partisipasi anonim terhadap dalam menguragi kecemasan dan meningkatkan interaksi kelas. Dengan menggunakan pendekatan deskriptif kuantitatif, penelitian ini melibatkan 94 mahasiswa Pendidikan Bahasa Inggris di sebuah universitas di Malang. Data dikumpulkan melalui kuesioner skala Likert berjumlah 11 item dan didistribusikan melalui Google Forms yang kemudian dianalisis menggunakan IBM SPSS Statistics 32. Hasil penelitian menunjukkan respons positif di seluruh indikator, dengan skor rata-rata berkisar antara 4,01 hingga 4,41. Berpartisipasi secara anonim terbukti dapat memberikan rasa aman dari kecemasan evaluasi negatif. Anonimitas juga terbukti efektif meningkatkan keterlibatan dan kualitas interaksi kelas, sehingga dapat menjadi pilihan strategi pembelajaran bagi dosen EFL di perguruan tinggi indonesia untuk menciptakan kelas yang lebih nyaman dan inklusif.